Self Concepts and Motivation To Learn Among Students - Yahaya, Azizi (2004)
Abtract: In Malaysia, more than half of the population are adolescent and most of them are students who are still studiying either in schools or in higher institutions of learning. We should be proud that eventhough there is no punishment to enforce education , 99 percent of the schooloing age children are getting their education. Wether they are willing to learn or reach level depend on many factors. For now, most of the students learn just to pass their exam and not learning continuosly through life as we hope for. Is it because the students are not motivated to learn because of their negative self concept ? or is it the teachers and parents who cause the students not to be motivated and encouraged to learn and excelled , what more to compete in education? The answer lies in all the significant people who should play their role in developing positive self concept to motivate students to learn.